Synthesis of Some new Sulfonamide Schiff’s Bases and Study Their Gastroprotective Activity - Almashal, Faeza (University of Thi-Qar Journal of Science, 2013)
Substituted sulfonamides were reacted with thiophene carbaldehydes and piperenal to form Schiff’s bases. The structures of synthesized compounds were confirmed by their IR,1 H NMR spectroscopic data and mass spectra.Different necrotizing agents (80% ethanol, 0.2 M NaOH and 25% NaCl) were used to induced gastric lesions. The compounds were given orally 30 min before the administration of necrotizing agents. The percentages for compounds to ulcer protective were calculated. Compound 4 was more effective than other compounds and omeprazole itself.Compound 1 was approximate equal to omeprazole activity, and after thatcompounds 3 and 2 respectively were less active.